Climate Change Adaptation Strategies among Coastal Community - Haijjon, Gunggut; Poline, Bala; Gaim, James Lunkapis; Roger W., Harris (AMER & cE-Bs by e-International Publishing House, Ltd., UK., 2024)
Using seven themes of adaptability strategies drawn from existing literature, this study examines the strategies for adaptation among the Bajau community in Lok Nunuk to cope with the impacts of climate change in the area. Questionnaires were distributed to 60 household heads, and descriptive statistics were used to analyze the data. The four obvious adaptation strategies identified in this study are social-related activities, physical infrastructure, technology-assisted, and government and organization support. There needs to be more than adaptation strategies to improve income among the people; they must be integrated into broader socioeconomic development programs and environment management levels.